Fitness parameters in professional football players among different divisions - Michaelides, M.; Koulla, P.; Evripidoy, D.; Zacharia, A.; Petousis, C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
The purpose of the study was to determine aspects of fitness that differentiate first division professional football players from players of second and third divisions in Cypriot football leagues. METHODS: Four hundred and twenty seven professional male football players (age =25 ± 5 years) performed an isokinetic knee test using the Humac Norm dynamometer at two angular velocities (60°/s, 300°/s). On a different occasion, they performed an incremental cardiopulmonary exercise testing (CPET) on a treadmill. Furthermore, anthropometric and flexibility (sit and reach) measurements were recorded. RESULTS: Results were analyzed using one-way ANOVA, between subjects design revealing significant effects for division. Tukey`s HSD tests demonstrated that players from division 1 scored significant higher on maximal oxygen consumption (VO2 max) and lasted significantly longer on the treadmill than participants of division 2 and 3 (p<0.05). Similar findings were demonstrated when division 2 was contrasted against division 3 players. Marginal or no significant differences were recorded among players from the three different divisions on anthropometric measurements, flexibility and isokinetic parameters (muscular strength and muscular endurance). The marginal differences observed were mainly between first and third division players. CONCLUSION: The findings of this study clearly demonstrated that cardiovascular fitness as determined by CPET is the most important fitness parameter that differentiates professional football players who play at a more advanced championships. Although, strength and muscular endurance of the knee joint as well as low back- hamstring flexibility parameters are crucial for performance and injury prevention in football, they appear to be similar in players from smaller divisions too. ABSTRACT FROM AUTHOR